2023
DOI: 10.3847/1538-4357/acb153
|View full text |Cite
|
Sign up to set email alerts
|

The Direct-method Oxygen Abundance of Typical Dwarf Galaxies at Cosmic High Noon∗

Abstract: We present a Keck/MOSFIRE rest-optical composite spectrum of 16 typical gravitationally lensed star-forming dwarf galaxies at 1.7 ≲ z ≲ 2.6 (z mean = 2.30), all chosen independent of emission-line strength. These galaxies have a median stellar mass of log ( … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 113 publications
(370 reference statements)
1
3
0
Order By: Relevance
“…Along these lines, accounting for sample variance suggests a large scatter in R(S II) at a given M * . Indeed, Gburek et al (2023) find an average n e consistent with the low-density limit (〈n e 〉 ; 1 cm −3 ) for a sample of lensed star-forming galaxies at z ∼ 2.3 with a median stellar mass of…”
Section: Stellar Mass Considerationssupporting
confidence: 63%
“…Along these lines, accounting for sample variance suggests a large scatter in R(S II) at a given M * . Indeed, Gburek et al (2023) find an average n e consistent with the low-density limit (〈n e 〉 ; 1 cm −3 ) for a sample of lensed star-forming galaxies at z ∼ 2.3 with a median stellar mass of…”
Section: Stellar Mass Considerationssupporting
confidence: 63%
“…We supplement this sample with a [O III]λ4364-detected galaxy from Gburek et al (2019) and two galaxies with detected [O II] auroral emission lines presented in Sanders et al (2023a). We do not include composite spectra (e.g., Steidel et al 2016;Gburek et al 2023), but instead limit to individual sources. The groundbased auroral-line sample thus includes 21 galaxies with a redshift distribution shown by the blue histogram in Figure 1, spanning z = 1.42 − 3.63.…”
Section: Ground-based Auroral-line Samplementioning
confidence: 99%
“…The most robust resolution to this problem is to construct high-redshift metallicity calibrations using direct metallicity and strong-line measurements of high-redshift galaxies themselves. Based on deep ground-based spectroscopy of bright high-redshift line emitters, a sample of ∼20 star-forming galaxies at z = 1.4−3.7 with auroral-line detections and directmethod metallicities has been assembled, representing many nights of 8−10 m telescope time (Villar-Martín et al 2004;Christensen et al 2012aChristensen et al , 2012bBrammer et al 2012;Stark et al 2013;Bayliss et al 2014;James et al 2014;Stark et al 2014;Sanders et al 2016b;Kojima et al 2017;Berg et al 2018;Patrício et al 2018;Gburek et al 2019;Sanders et al 2020;Gburek et al 2023;Sanders et al 2023a). Sanders et al (2020) showed that, on average, this sample deviates from calibrations based on normal z ∼ 0 sources, but it is wellmatched by the local analog calibrations of Bian et al (2018).…”
Section: Introductionmentioning
confidence: 99%
“…At redshifts of z ∼ 1-3, the MZR has been characterized down to stellar masses of log(M å /M e ) ≈ 9 (Maiolino et al 2008;Henry et al 2013;Kacprzak et al 2016;Ly et al 2016;Onodera et al 2016;Suzuki et al 2017;Wang et al 2020;Sanders et al 2021;Gburek et al 2023). Studies beyond the local Universe were previously limited to higher-mass galaxies due to the difficulty of observing optical emission lines at z > 1 from the ground that are required for metallicities (Clarke et al 2023), combined with the intrinsic faintness of low-mass galaxies.…”
Section: Introductionmentioning
confidence: 99%